2021
DOI: 10.1037/sgd0000441
|View full text |Cite
|
Sign up to set email alerts
|

Keeps me awake at night: The potential of the COVID-19 pandemic to affect sleep quality among sexual minority men in the U.S.A.

Abstract: Sleep health, a crucial component and predictor of physical and mental health, has likely been adversely impacted by the stress and disruption wrought by the COVID-19 pandemic. This brief report sought to assess self-reported sleep quality among sexual minority men across the United States in the early months of the pandemic. In a cross-sectional online survey of a racially diverse sample of 477 sexual minority men (mean age ϭ 41.2 years; range ϭ 18 -75 years) recruited from popular geosocial networking apps i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Ten studies detailed SGM. [86][87][88][89][90][91][92][93][94] Most reported an increase in anxiety or depression during the pandemic. 86-92 94 A crosssectional observational quantitative study found an increase in experiences of mental distress, anxiety or depression among American SGM college students.…”
Section: Sexual and Gender Minoritiesmentioning
confidence: 99%
“…Ten studies detailed SGM. [86][87][88][89][90][91][92][93][94] Most reported an increase in anxiety or depression during the pandemic. 86-92 94 A crosssectional observational quantitative study found an increase in experiences of mental distress, anxiety or depression among American SGM college students.…”
Section: Sexual and Gender Minoritiesmentioning
confidence: 99%
“…SMM have been found to experience elevated levels of COVID-19-related stress. Among a sample of SMM, pandemic-related worry has been linked to sleep disturbance (Millar et al, 2020 ). SMM have reported challenges with meeting basic resource needs during the pandemic, such as purchasing food and paying rent due to loss of employment and limited access to sexual healthcare (i.e., HIV and STI testing, pre-exposure prophylaxis (PrEP) services, and HIV treatments; Banerjee & Nair, 2020 ; Brennan et al, 2020 ; Sanchez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the COVID-19 crisis had a greater psychological impact on sexual minority men, as had been hypothesised early on in the crisis [4,6]. Because earlier research had reported the high impact of the COVID-19 crisis on sexual minority men [24][25][26][27], but also on the general population [28], it was therefore important to test whether sexual minority men were more affected than heterosexual men. To the best of our knowledge, only three studies, based on online convenience samples from the United States of America [7,29,30], had reported a higher psychological impact of the COVID-19 crisis among sexual minorities compared to heterosexual people.…”
Section: Discussionmentioning
confidence: 97%
“…Their existing higher addictive behaviours and substance use [9] may also be further exacerbated as a coping mechanism for COVID-19's psychological impact. Recent research has indicated that members of sexual minority groups have suffered a high psychological impact from the crisis [24][25][26][27], but these studies were done in samples of sexual minority people only and, therefore, that impact cannot be compared with the psychological impact suffered by the heterosexual people also affected by the crisis [28]. Only three studies with online recruited convenience samples from the United States of America comparing sexual minorities and heterosexual persons found that the psychological impacts among members of sexual minorities were greater [7,29,30].…”
Section: Introductionmentioning
confidence: 99%